2014
DOI: 10.1136/heartjnl-2013-304914
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output response and peripheral oxygen extraction during exercise among symptomatic hypertrophic cardiomyopathy patients with and without left ventricular outflow tract obstruction

Abstract: Cardiac reserve is reduced in HCM because of failure of SV augmentation. LVOTO exacerbates this abnormal response, but haemodynamic responses vary significantly. Non-invasive exercise haemodynamic assessment may improve understanding of symptoms and help tailor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Our studies in patients from a family carrying the R403Q mutation in myosin heavy chain (MHC) revealed a 43% reduction in forward CK flux at rest, indicating reduced metabolic reserve (Abraham et al, 2013). A recent study by Critoph et al revealed reduced cardiac reserve secondary to blunted increase in cardiac output, in HCM patients undergoing exercise stress testing (Critoph et al, 2014). NMR studies in mice with R403Q-MHC (Spindler et al, 1998) and R92-TNT (Javadpour et al, 2003; He et al, 2007) mutations verified impaired myocardial energetics during inotropic stimulation.…”
Section: Evidence Of Hcm As a Metabolic Diseasementioning
confidence: 99%
“…Our studies in patients from a family carrying the R403Q mutation in myosin heavy chain (MHC) revealed a 43% reduction in forward CK flux at rest, indicating reduced metabolic reserve (Abraham et al, 2013). A recent study by Critoph et al revealed reduced cardiac reserve secondary to blunted increase in cardiac output, in HCM patients undergoing exercise stress testing (Critoph et al, 2014). NMR studies in mice with R403Q-MHC (Spindler et al, 1998) and R92-TNT (Javadpour et al, 2003; He et al, 2007) mutations verified impaired myocardial energetics during inotropic stimulation.…”
Section: Evidence Of Hcm As a Metabolic Diseasementioning
confidence: 99%
“…Because diastolic dysfunction reduces the filling of the left ventricle, the heart cannot pump enough blood to satisfy the needs of the body when exercising, thus causing damage to the heart due to exercise intolerance and raised LVFP [ 25 , 26 ]. However, it is also possible that the cause of exercise intolerance might be secondary to the inability of the stroke volume to increase appropriately because of abnormal sarcomeric protein causing abnormal contractility and reduced inotropic reserve [ 26 , 27 ]. We observed that HCM patients had higher E/Em, VE/VCO2 slope and lower VO2max.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial cells collected from patients subjected to surgical myectomy had a defective response to stretch in vitro irrespective of the mutated gene (Sequeira et al, 2013 ). During exercise, HCM patients failed to increase stroke volume in part due to this defect (Critoph et al, 2014 ). An MYL3 HCM mutation in a mouse study affected the frequency range at which the heart can operate efficiently due to alteration of the stretch-activation response (Vemuri et al, 1999 ).…”
Section: Mechanical Flaws In Hcm Patientsmentioning
confidence: 99%